Silences, diatribes and supports. The intellectual left against the Malvinas War - Moretti, Ignacio (Universidad Nacional del Litoral, 2018)
How the intellectual left was positioned in front of the Malvinas War? What conceptual maps and comprehensive frameworks supported their positioning? Does the core explanatory variable about their dissimilar public postures against the war refer to their differential intellectual and ideological trajectories or to other circumstances? This article seek to explain, describe and analyze the positions of a diverse group of leftist intellectuals that represent different special configurations, ideological belongings and paths, and which have generally not been privileged object of specialized approaches: the review Punto de Vista, intellectual group of the review Testimonio Latinoamericano and Néstor Perlongher.